Lightning‐caused disturbance in the Peruvian Amazon. (23rd July 2020) - Gora, Evan M.; Yanoviak, Stephen P.
Abstract: We surveyed seven lightning strike sites in the northern Peruvian Amazon. An average of 17.3 trees were damaged per strike; large trees (> 60 cm diameter) were disproportionately affected. The results contribute to a growing body of evidence that lightning is an important agent of disturbance pantropically. Abstract in Spanish is available with online material. Resumen: Se revisaron siete sitios golpeados por rayos en la Amazonia peruana. En promedio 17.3 árboles fueron afectados por rayo; de estos, los arboles grandes (>60 cm de diámetro) fueron desproporcionadamente afectados. Estos resultados contribuyen a una creciente evidencia de que los rayos son agente importante de perturbación en bosques tropicales.